Properties of bio-composite lumber from oil palm fronds agriculture waste - Razak Wahab; Mohd Sukhairi Mat Rasat; Othman Sulaiman; Izyan Khalid (2011)
The physical and mechanical properties of bio-composite lumbers from agricultural residues of oil palm fronds were studied. Phenol and urea formaldehyde were used as the binders. The oil palm fronds were obtained from an oil palm plantation. The fronds were harvested and segregated into matured, intermediate and young grouping. The fronds were then sub-segregated into bottom, middle and top portions. The leaflets and the epidermis were removed from the fronds before they were sliced longitudinally into thin layers. The layers were then compressed into uniform thickness of 2-3 mm. The layers were air-dried and later mixed with resins using 12-15% of phenol and urea formaldehyde and recompressed with other layers forming bio-composite lumbers. The bio-composite lumbers were then tested for their physical and mechanical properties. Testing was conducted according to the standards of the International Organizational for standardization (ISO). The result on the physical and mechanical properties shows that the compressed oil palm fronds bio-composite lumbers is better than composite lumbers from oil palm trunks and slightly lower than the rubberwood. Statistical analysis indicated significant differences between bio-composite lumbers made from each groups and portion, but no differences were observed in the type of resin used. The bio-composite lumbers from compressed oil palm fronds agricultural redidues has potential to be used as an alternative to wood to overcome the shortage in materials in the wood industry.